Molecular characterization of a synthetic neutralizing antibody targeting p67 of Theileria parva - Miersch, S.; Singer, A.U.; Chen, C.; Fellouse, F.; Gopalsamy, A.; Costa, L.S. e; Lacasta, Anna; Chege, Hannah; Chege, Naomi; Nene, Vishvanath; Sidhu, S.S. (Wiley, 2025)
The Theileria parva sporozoite surface antigen p67 is a target of the bovine humoral immune response that generates antibodies capable of providing protection against subsequent infection. As a result, p67 has been the subject of efforts aimed at the development of an anti-sporozoite subunit vaccine. Previous studies have identified neutralizing epitopes in the N- and C-terminal regions of the full-length protein and shown that immunization with a C-terminal fragment of p67 (p67C) alone is capable of eliciting protection. To identify additional neutralizing epitopes in p67C, selections were conducted against it using a phage-displayed synthetic antibody library. An antibody that neutralized the sporozoite in vitro was identified, and the crystal structure of a Fab:peptide complex was elucidated. Mutagenesis studies aimed at validating and further characterizing the Fab:peptide interaction identified critical residues involved in binding and neutralization. This study also validates distinct epitopes for previously reported neutralizing antibodies.